Ketepatan Pemberian Opini Auditor: Survey Terhadap Auditor Di Provinsi Bali - Melliani, Ni Made Rian; Salim, Susanto (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
Audit opinion is a form of professional statement delivered by the auditor that expresses an assessment of the fairness of the presentation of the entity’s financial statements based on generally accepted accounting standards. The accuracy of the auditor in providing an audit opinion plays an important role in building and maintaining public trust in the accounting profession. The opinion given in the audit report will be used by internal and external parties who are affected or interested in the contents of the financial statements of the related entity as a basis for decision making. This study is intended to test the auditor’s expertise, audit experience, independence, and professional skepticism on the accuracy of providing audit opinions at KAP operating in the Bali Province. The population and sample of this study were 84 auditors who actively practice at the Bali Province Public Accounting Firm. This study uses a purposive sampling method with data collected through questionnaires, and data analysis is carried out using multiple linear regression. This study shows that audit experience, independence and professional skepticism have a positive effect on the accuracy of providing audit opinions, while auditor expertise does not show any significant effect on the accuracy of providing audit opinions.